Analysis of Financial Distress in Telecommunication Companies in Indonesia Using the Ohlson O-Score and Zmijewski Methods - Bayyinah, Ayyinah Nur (Research Collaboration Community (RCC), 2025)
Currently, major telecommunication sub-sector companies in Indonesia are experiencing rapid growth and have become dominant players in the market. However, not all telecommunication companies are profitable, as some dominant subsidiaries have experienced declining profits or losses, potentially leading to financial distress. Financial distress is a condition where a company is unable to meet its current obligations, such as trade payables, tax liabilities, and short-term debts. This study aims to analyze and evaluate the accuracy of the Ohlson O-Score and Zmijewski methods in detecting financial distress in telecommunication companies in Indonesia. The data used in this study are historical financial data from several telecommunication companies listed on the Indonesia Stock Exchange. The results show that the Ohlson O-Score is effective in early detection of potential financial distress, while the Zmijewski method is more effective in evaluating companies already in critical financial conditions.